082 Safety of ondansetron in a case series of patients with a predisposition to seizures. Issue 12 (14th November 2019) - White, Laura; Pipe, Michelle; Hayton, Tom; Barnes, Nicholas
Abstract : Background: Patients with temporal lobe epilepsy and hippocampal sclerosis (TLE-HS) have increased hippocampal 5-hydroxytryptamine (5HT)-3 receptors versus controls. 5HT-3 antagonists may therefore be efficacious in TLE-HS. However, rare case reports have described seizures in patients treated with 5HT-3 antagonists. We retrospectively investigated seizure episodes in patients with a seizure predisposition treated with ondansetron. Methods: Inpatients admitted to the West Midlands regional neurosciences centre from 08/09/2015–31/01/2017 with an epilepsy diagnosis or prescribed ≥1 antiepileptic drug and treated with ondansetron for ≥4 days were included. Patient notes were reviewed to identify seizure episodes during ondansetron treatment. Results: 50 patients were identified; 14 had epilepsy, 36 had other diagnoses predisposing to seizures. During ondansetron treatment, 21.4% epilepsy patients and 11.1% with other diagnoses experienced ≥1 seizure; all seizures were deemed unlikely to be ondansetron related. Patients with seizures had similar treatment duration versus patients without (median 8 vs 6 days) and a lower cumulative dose (median 56 vs 72 mg). Conclusion: Three patients with epilepsy and four with other diagnoses experienced seizures during ondansetron treatment; none of the seizures were thought to be ondansetron related. A randomised controlled study is needed to assess the efficacy and safety of ondansetron in patients with epilepsy.